Measuring and modeling waterlogging tolerance to predict the future for threatened lowland ash forests - E. J. Gustafson; D. R. Bronson; M. A. Windmuller-Campione; R. A. Slesak; D. M. Donner (Biogeosciences)
The emerald ash borer is an invasive pest causing widespread mortality of ash trees (Fraxinus spp.) across the USA. Broad-scale models can help identify management strategies to maintain lowland ash ecosystems. Simulating lowland forest dynamics in landscape models has been problematic because lowland hydrology is extremely complex, making most hydrology algorithms intractable at the landscape scale. A succession extension (PnET-Succession) of the LANDIS-II forest landscape model was recently updated to include simple algorithms to approximate lowland hydrology, but estimating parameters of tree species' waterlogging tolerance is difficult. We describe empirical experiments conducted to generate such estimates and illustrate their behavior in single-cell and landscape simulations. Simulated water stress mimicked two critical characteristics of the empirical experiment: (1) there was little difference in simulated stress variables between the well-drained and intermediate flooding treatments, and (2) simulated water stress of species aligned with empirical waterlogging tolerance. We used the landscape model to scale the empirical experiment to landscape scales of space and time. When the simulation experiment was extended to 90 years, species productivity plateaued or peaked at a level that could be supported by the precipitation inputs and rooting zone depth. In a virtual experiment testing the competition outcomes between two species, the more-waterlogging-tolerant species did much better under the flooding treatment, but also tended to do better under the drained treatment because it never produced droughty conditions. When the updated waterlogging parameters were applied at landscape scale under future climate change and assisted migration (AM) scenarios, the mean biomass density of native species declined, and the introduced AM species increased as the climate gradually changed and introduced cohorts thrived. Species that are waterlogging tolerant were able to persist under all assisted migration–climate change scenarios and to a limited extent were able to colonize (and ephemerally dominate) upland sites. Well-parameterized landscape models provide a powerful tool to conduct simulation experiments involving novel situations such as climate change, invasive (or intentionally migrated) tree species, invasive insects or diseases, and proposed management strategies.